2006
DOI: 10.1120/jacmp.v7i1.2162
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characteristics of a new linear accelerator under gated operation

Abstract: Respiratory gated radiotherapy may allow reduction of the treatment margins, thus sparing healthy tissue and/or allowing dose escalation to the tumor. However, current commissioning and quality assurance of linear accelerators do not include evaluation of gated delivery. The purpose of this study is to test gated photon delivery of a Siemens ONCOR Avant‐Garde linear accelerator. Dosimetric characteristics for gated and nongated delivery of 6‐MV and 15‐MV photons were compared for the range of doses, dose rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Overall, linear accelerators appear very accurate at delivering dose in gated modes, for static as well as dynamic deliveries. ( 8 , 14 18 ) Our results are consistent with these findings. A few articles have addressed the measurement of time delays.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, linear accelerators appear very accurate at delivering dose in gated modes, for static as well as dynamic deliveries. ( 8 , 14 18 ) Our results are consistent with these findings. A few articles have addressed the measurement of time delays.…”
Section: Discussionsupporting
confidence: 92%
“…Thus these measurements are consistent with the Varian data. Kriminski et al (2006) studied gating of the Siemens ONCOR system. They also studied a range of gating periods with 50 % duty cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have reported gating results for three manufacturers: Varian Wang 2000 andJin andYin 2005); Siemens (Kriminski et al 2006 andWeibert et al 2009) and Brainlab (Hugo et al 2003 andVerellen et al 2003). The Varian system uses a gridded gun for gating.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, since dose calculations for treatment planning are usually based on data gained for ungated irradiation, it is very important to check whether gating influences the beam characteristics of the linear accelerator before introducing respiratory gating into clinical routine [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%